2019
DOI: 10.1038/s41598-018-36841-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and evaluation of inhibitor of LARP6 as specific antifibrotic compound

Abstract: Fibrosis is characterized by excessive production of type I collagen. Biosynthesis of type I collagen in fibrosis is augmented by binding of protein LARP6 to the 5′ stem-loop structure (5′SL), which is found exclusively in type I collagen mRNAs. A high throughput screen was performed to discover inhibitors of LARP6 binding to 5′SL, as potential antifibrotic drugs. The screen yielded one compound (C9) which was able to dissociate LARP6 from 5′ SL RNA in vitro and to inactivate the binding of endogenous LARP6 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 73 publications
(70 reference statements)
1
23
0
Order By: Relevance
“…In addition to the well-known activated HSCs markers, some of the most significant DEGs that were identified by RNA sequencing played a critical role in HSC activation or liver fibrosis. Among these genes, CDH11 [22,23], CTHRC1 [24], FMOD [25], and PRRX1 [26] facilitated HSC activation; Larp6 promoted type I collagen production and was a potential anti-fibrotic target [27,28]; HHIP, a Hedgehog pathway antagonist, inhibited HSC activation and was downregulated in activated HSCs [29]. Moreover, we also evaluated the changes in the expression of the most significant DEGs in TGF-β1-treated LX-2 cells, which is an in vitro human HSC activation model ( Fig 4F).…”
Section: Rna Sequencing Of Quiescent and Activated Primary Hscsmentioning
confidence: 99%
“…In addition to the well-known activated HSCs markers, some of the most significant DEGs that were identified by RNA sequencing played a critical role in HSC activation or liver fibrosis. Among these genes, CDH11 [22,23], CTHRC1 [24], FMOD [25], and PRRX1 [26] facilitated HSC activation; Larp6 promoted type I collagen production and was a potential anti-fibrotic target [27,28]; HHIP, a Hedgehog pathway antagonist, inhibited HSC activation and was downregulated in activated HSCs [29]. Moreover, we also evaluated the changes in the expression of the most significant DEGs in TGF-β1-treated LX-2 cells, which is an in vitro human HSC activation model ( Fig 4F).…”
Section: Rna Sequencing Of Quiescent and Activated Primary Hscsmentioning
confidence: 99%
“…LARP6 is the specific regulator of translation of type I collagen mRNAs and recognition of 5'SL of collagen mRNAs by LARP6 is critical for fibrosis development [27,28]. Therefore, LARP6 binding inhibitors show promise as antifibrotic compounds [28], because they overcome the main drawback of antifibrotic drugs currently in development; the lack of specificity. This work provides insight into the molecular recognition between LARP6 and 5'SL, as the first step to help rational design of such inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being more invasive, these subtypes often exhibit a greater resistance to standard chemotherapies, collectively resulting in poorer outcome (Dongre and Weinberg, 2019). Importantly, we have shown that 800 a small molecule compound named C9 which interferes with LARP6 RNA binding activity (Stefanovic et al, 2019) can also inhibit RP-mRNA localization to protrusions. Although the safety, efficacy, and pharmacological properties of C9 may not be satisfactory for use in clinic, our results demonstrate the plausibility of therapeutic targeting of LARP6 by small-molecule inhibitors in the context of inhibiting ribosome biogenesis in mesenchymal/EMT associated 805 cancer subtypes.…”
mentioning
confidence: 88%
“…Importantly, recent work has demonstrated that LARP6 can be targeted by specific small molecule inhibitors designed to interfere with its substrate binding. One such 715 compound, named C9, has been shown to inhibit LARP6 binding to the 5′ stem-loop of Collagen-I mRNA at nano-molar (nM) concentrations (Stefanovic et al, 2019). To test whether C9 could similarly inhibit LARP6 function in the context of RP-mRNAs, we tested the effect of C9 treatment on RP-mRNAs localization to protrusions.…”
Section: ____________________________________________________________mentioning
confidence: 99%